PENGARUH KOMUNIKASI DIALOGIS DAN RESPONSIVITAS LAYANAN PENGADUAN TERHADAP KEPERCAYAAN MASYARAKAT PADA KOMISI KEJAKSAAN REPUBLIK INDONESIA - Johannes Ronald Elyeser Roparulian Hutagalung; Diajeng Herika Hermanu (Jurnal Spektrum Komunikasi, 2025)
Public trust in law enforcement supervisory agencies is an important foundation for democracy and the rule of law in Indonesia. The Indonesian Attorney General's Commission, as an independent agency that supervises the performance of the attorney general's office, faces the challenge of building credibility and public trust through effective communication and optimal responsiveness to complaints. This study aims to determine the influence of dialogic communication and responsiveness to complaints on public trust in the Indonesian Attorney General's Commission. The study used a survey method with 120 respondents using purposive sampling. Dialogic communication includes mutuality orientation and an atmosphere of openness, while complaint service responsiveness includes speed of response, consistency of follow-up, and transparency of the process. The data were analyzed using multiple regression analysis with SPSS version 26. The results showed that dialogic communication and complaint service responsiveness had a significant effect on public trust of 89.0% with an F-statistic = 471.44 (p < 0.001). Dialogic communication had a significant effect with a correlation of r = 0.9203 (t = 25.55, p < 0.001), while the responsiveness of complaint services had a significant effect with a correlation of r = 0.9167 (t = 24.91, p < 0.001). The findings confirm the importance of dialogic communication and responsive services in increasing public trust in law enforcement supervisory agencies in Indonesia.